Successful clozapine rechallenge after myopericarditis: a case report. (30th May 2022) - Boscutti, Andrea; Cereda, Guido; Lazzaretti, Matteo; Enrico, Paolo; Fiorentini, Alessio; Prunas, Cecilia; Callari, Antonio; Fontana, Elisa; Delvecchio, Giuseppe; Brambilla, Paolo
Abstract : Clozapine-induced myocarditis and pericarditis are uncommon adverse effects of clozapine treatment. However, in most cases, they lead to clozapine discontinuation. Here, we describe a case of successful clozapine rechallenge after clozapine-induced myopericarditis. The patient, a 31-year-old male with treatment-resistant schizophrenia (TRS), developed dyspnea on exertion and chest pain on day 19 after the start of clozapine titration. An electrocardiogram (ECG) showed widespread, mild, convex ST interval elevation. While troponin levels were mildly elevated, the echocardiogram was unremarkable. A myopericarditis diagnosis was formulated, and clozapine was stopped, with a progressive resolution of clinical, laboratory and ECG abnormalities. After 6 months, a rechallenge with clozapine was attempted. A very slow titration scheme was adopted, along with close monitoring of clinical, laboratory and ECG parameters. Clozapine target dose was reached without the occurrence of any abnormality. Given the unique role of clozapine in the management of TRS, clozapine rechallenge may be considered after pericarditis, even with troponin levels elevation. Further studies are needed to update current clinical guidelines.